Infertility treatment outcome in sub groups of obese population - Al Deery Mashael A; Al Hassan Saad H; Nahas Samar; Awartani Khalid A; Coskun Serdar (BMC, 2009)
Abstract Background Obesity is a common disorder with a negative impact on IVF treatment outcome. It is not clear whether morbidly obese women (BMI >= 35 kg/m2) respond to treatment differently as compared to obese women (BMI = 30-34.9 kg/m2) in IVF. Our aim was to compare the outcome of IVF or ICSI treatments in obese patients to that in morbidly obese patients. Methods This retrospective cohort study was conducted in a tertiary care centre. Patients inclusion criteria were as follows; BMI ≥ 30, age 20-40 years old, first cycle IVF/ICSI treatment with primary infertility and long follicular pituitary down regulation protocol. Results A total of 406 obese patients (group A) and 141 morbidly obese patients (group B) satisfied the inclusion criteria. Average BMI was 32.1 ± 1.38 kg/m2 for group A versus 37.7 ± 2.99 kg/m2 for group B. Patient age, cause of infertility, duration of stimulation, fertilization rate, and number of transferred embryos were similar in both groups. Compared to group A, group B had fewer medium size and mature follicles (14 vs. 16), fewer oocytes collected (7 vs. 9) and required higher doses of HMG (46.2 vs. 38.5 amps). There was also a higher cancellation rate in group B (28.3% vs. 19%) and lower clinical pregnancy rate per started cycle (19.9% vs. 28.6%). Conclusion In a homogenous infertile and obese patient population stratified according to their BMI, morbid obesity is associated with unfavorable IVF/ICSI cycle outcome as evidenced by lower pregnancy rates. It is recommended that morbidly obese patients undergo appropriate counseling before the initiation of this expensive and invasive therapy.